2018
DOI: 10.1093/conphys/coy057
|View full text |Cite
|
Sign up to set email alerts
|

A burning question: what are the risks and benefits of mammalian torpor during and after fires?

Abstract: Although wildfires are increasing globally, available information on how mammals respond behaviourally and physiologically to fires is scant. Despite a large number of ecological studies, often examining animal diversity and abundance before and after fires, the reasons as to why some species perform better than others remain obscure. We examine how especially small mammals, which generally have high rates of energy expenditure and food requirements, deal with fires and post-fire conditions. We evaluate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 124 publications
1
15
0
Order By: Relevance
“…Sleepy lizards aren't alone-a growing diversity of animal species from fire-prone landscapes have been found to sense incipient fire (Geiser et al, 2018;. This capacity to detect, recognise, and respond to olfactory cues raises obvious parallels with another widespread and lethal selective force-predation.…”
Section: Where There's Smoke…mentioning
confidence: 99%
See 1 more Smart Citation
“…Sleepy lizards aren't alone-a growing diversity of animal species from fire-prone landscapes have been found to sense incipient fire (Geiser et al, 2018;. This capacity to detect, recognise, and respond to olfactory cues raises obvious parallels with another widespread and lethal selective force-predation.…”
Section: Where There's Smoke…mentioning
confidence: 99%
“…That 13 other species in the same room did not react suggests that the sleepy lizard's response is probably not merely a generic response to novel stimuli but a fine-tuned response to a cue with a specific interpretation. While most other examples of animals responding to fire cues come from wildcaught animals (Geiser et al, 2018)-and therefore cannot distinguish between learned and innate responses-captive bred fat-tailed dunnarts (Sminthopsis crassicaudata) arouse from torpor when exposed to smoke, also suggesting an innate response (Stawski, Matthews, et al, 2015).…”
Section: Fire Ecology Meets Predator Ecologymentioning
confidence: 99%
“…However, complications may arise for the many mammalian and avian species that employ torpor (a temporal reduction in metabolic rate and body temperature) during winter in response to a decrease in temperature and resource availability. While some torpid mammals are able to respond to fi re cues such as smoke, their responses are often slowed at colder temperatures [7]. Therefore, these torpid animals would be at risk of mortality during winter management burns conducted at very cold temperatures, as they would be less likely to rewarm from torpor and escape.…”
Section: A Physiological Understanding Of Organismal Responses To Fi Rementioning
confidence: 99%
“…Therefore, these torpid animals would be at risk of mortality during winter management burns conducted at very cold temperatures, as they would be less likely to rewarm from torpor and escape. Studies conducted in Australia also revealed that some small terrestrial mammals become energetically constrained even after mild fi res that only reduce ground cover and understorey vegetation [7]. Conversely, some bats are less energetically constrained as they are able to take advantage of the more open foraging conditions.…”
Section: A Physiological Understanding Of Organismal Responses To Fi Rementioning
confidence: 99%
See 1 more Smart Citation